Ethnobotanical study on forage plants of Baiku Yao in China - Renchuan HU; Qimin HU; You NONG; Binsheng LUO (Guangxi Zhiwu, 2023)
Baiku Yao like to raise and eat local black pigs, and they are very good at collecting and managing forage plants. This study aimed to make an ethnobotanical inventory of forage plants and their related native knowledge in the Baiku Yao area, provide data support for the preservation of their traditional knowledge, and provide ideas for the development of modern new types of forage. From 2019 to 2021, we went to the local area for ethnobotanical investigation of forage plants, using key formant interviews, semi-structured interviews, and group discussions. Additionally, we had screened out the forage plants with high comprehensive utilization value according to scoring and ranking and their usage frequency. The results were as follows: (1) A total of 104 forage plant species were recorded, belonging to 42 families and 85 genera. The family with the most cited species was Asteraceae (16 species, accounting for 15.38% of the total species), followed by Urticaceae (13 species, accounting for 12.5% of the total species). (2) Branches and leaves (56.73%), whole plant (26.92%) and leaves (8.65%) were the main used parts of local forage plants, accounting for 92.30% of the recorded plants. Most forage plants were herbaceous plants (88.46%). There were adequate forage plants (accounting for 64.42% of the total) that could be collected to feed pigs in almost all seasons. (3) Chopping, crushing, and cooking feed plants were the main preparation methods of pig forage. (4) The most frequently cited local species were Zea mays, Broussonetia papyrifera, Ipomoea batatas, Morus alba, Fagopyrum dibotrys and Oryza sativa. (5) The local forage plants with high comprehensive evaluation were Broussonetia papyrifera, Ipomoea batatas, Morus alba, Fagopyrum dibotrys and Cucurbita moschata. The local people have rich traditional knowledge about the use and management of forage plants for pigs, which are very scientific and well preserved, and the related forage plant resources are also worthy of further development and promotion.